2018
DOI: 10.1155/2018/1340479
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Future Need of Walking Device or Assistance by Moderate to Vigorous Physical Activity: A 2-Year Prospective Study of Women Aged 75 Years and Above

Abstract: Objective To examine the association between daily moderate to vigorous physical activity (MVPA) and the change in mobility function among community-dwelling Japanese women aged 75 years and above. Methods This prospective study included 330 older women aged 75 years and above who could walk without a walking device or assistance. MVPA and light-intensity physical activity (LPA) were assessed using an accelerometer for seven consecutive days. MVPA was defined as an activity with an intensity of >3 metabolic eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…A total of 34 studies were retained for inclusion. [ 6 , 7 , 21 – 52 ] An additional nine studies were identified through secondary sources [ 53 61 ], resulting in a final sample of 43 studies (see Figure 1 ).
Fig 1.
…”
Section: Resultsmentioning
confidence: 99%
“…A total of 34 studies were retained for inclusion. [ 6 , 7 , 21 – 52 ] An additional nine studies were identified through secondary sources [ 53 61 ], resulting in a final sample of 43 studies (see Figure 1 ).
Fig 1.
…”
Section: Resultsmentioning
confidence: 99%
“…This may be especially important for populations such as the elderly or chronically ill, where high-intensity PA might be difficult to achieve for a variety of reasons. 40 , 39 In addition, a change in the intensity of PA within a 24-h daily schedule without changing other components (i.e. SB and sleep) may be an effective strategy to improve some health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The non-wear time was defined as no acceleration signal obtained for more than 60 min. Only accelerometer data for more than 5 valid days, with at least 10 wearing hours per day, were adopted, and the average duration of PA for each intensity was calculated and used for the analysis 26 ) .…”
Section: Participants and Methodsmentioning
confidence: 99%